2021
DOI: 10.1186/s13018-021-02305-9
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin modulates catabolic cytokine expression through Sirt1 and SOX9 in human articular chondrocytes

Abstract: Background Silymarin (SMN), a polyphenolic flavonoid, is involved in multiple bioactive functions including anti-inflammation. Pretreatment with SMN demonstrated chondroprotection against tumour necrosis factor-alpha (TNF-α) stimulation in a chondrocyte cell line. However, pre- and posttreatment with phytochemicals have varying effects on osteoarthritis (OA) chondrocytes, and the therapeutic potential of SMN after catabolic cytokine stimulation is not fully elucidated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…These studies suggest that SIRT1 is not necessarily protective in AMD and is more likely to be two-sided. Previous studies have revealed that SIRT1 acts as a deacetylase with many downstream substrates, such as p65 NF- κ B [ 40 ], STAT3 [ 41 ], and CHK2 [ 42 ], SOX9 [ 43 ], and plays different roles in various biological processes mainly for deacetylation of histones and nonhistones with different mechanisms of action. Thus, the substrates regulated by SIRT1 deacetylation are all transcription factors, and the regulation of target genes by transcription factors is strongly dependent on the cellular and disease environment.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that SIRT1 is not necessarily protective in AMD and is more likely to be two-sided. Previous studies have revealed that SIRT1 acts as a deacetylase with many downstream substrates, such as p65 NF- κ B [ 40 ], STAT3 [ 41 ], and CHK2 [ 42 ], SOX9 [ 43 ], and plays different roles in various biological processes mainly for deacetylation of histones and nonhistones with different mechanisms of action. Thus, the substrates regulated by SIRT1 deacetylation are all transcription factors, and the regulation of target genes by transcription factors is strongly dependent on the cellular and disease environment.…”
Section: Discussionmentioning
confidence: 99%
“…Chondrocyte senescence can be regulated by IL-1β. Silymarin has been shown to improve IL-1β-stimulated cell senescence, decrease catabolic gene expression, and restore chondrogenic phenotype factor expression ( 130 ). The senescence-associated secretory phenotype (SASP) is associated with the biological actions of senescent cells in producing inflammation-promoting factors.…”
Section: Natural Flavonoids Exhibit Protective Activity Against Oa De...mentioning
confidence: 99%
“…218,219 Silymarin has the ability to increase hepatic SIRT1 expression. 220 Silymarin can also increase SIRT1 expression in other tissues, such as hippocampus, 221 articular chondrocytes, 222 and heart muscle. 223 Silymarin seems to act differently in tumors: in lung cancer cells SIRT downregulated SIRT1 and exerted multiple antitumor effects such as reduced adhesion and migration and increased apoptosis.…”
Section: Silymarin and Sirt1mentioning
confidence: 99%